Raman spectroscopy as a versatile tool to study organic biradicals - Zafra-Paredes, Jose Luis (My University, 2018)
In recent years, there has been a renewed interest in the study of open-shell polycyclic aromatic hydrocarbons (PAHs). Among them, biradicals are characterized by a four states energetic model for the low lying electronic states S0, S1, S2, T1. Such a distribution is related to the attractive electronic, magnetic and optical properties which make biradicals promising candidates for a wide range of applications in organic electronics, such as nonlinear optics, molecular spintronics, energy storage and organic photovoltaic devices sensitized by singlet fission. Despite all the promising properties predicted for open-shell PAHs, a common drawback still needs to be overcomed: the high reactivity of radicals, which implies that most open-shell species tend to be too short-lived for practical aplications and even for characterization [1]. In this regard, Raman spectroscopy has shown to be a suitable tool for studying this kind of molecular systems, able to provide valuable information that could be used in the development of new synthetic approaches [2].
Comunicación científica
Keywords: Espectroscopia Raman; Estructura electrónica; Raman spectroscopy; Diradical; Electronic structure